Simulasi Efek Ukuran dan Lokasi Kebocoran Pipa Pendingin Reaktor Nuklir Menggunakan Fasilitas Eksperimen UUTR.Mod-l - Antariksawan, Anhar R.; Juarsa, Mulya; Prasetyo, Joko; Sumarno, Edy; Kiswanta, Kiswanta; Handoyo, Ismu (Program Studi Teknik Mesin, Universitas Trisakti, 2007)
Experimental Simulation of The Effect of Size and Location of Coolant Pipe Break inNuclear Reactor Using UUTR.Mod-l. Several experiments of LOCA with various break size andlocations have been conducted using UUTR.Mod-l testfacility. The break sizes studied are 2 mm, 5 mmand 10 mm, each at hot-leg and cold-leg side. The initial conditions ofthe experiment are 1 MWofpower,primary side pressure of 155 bar approximately, coolant flow rate of 9.8 kg/s and only accumulator isfunctioned as emergency coolant. Both at hot-leg and cold-leg, the break size of 2 mm showed slowerpressure decrease rate and the occurrence of temperature increase early after break. For larger breaksize, pressure decrease is faster and showed rod temperature excursion due to rod uncovering.Concerning the breaklocation, in large break area, cold-leg breakshowed heater temperature excursionearly than in case of hot-leg break. Size and location of break determine the timing of event and, asconsequence, different behavior of response system. In any cases to prevent the fuel temperatureexcursion, the addition ofautomatic depressurizationsystem and installation ofinjection system in upperhead ofpressure vessel have been consideredin the nuclearreactor design.